Experimental Study of Concrete Making Using Recycled Coarse Aggregate - Moch Reza Maskur; Zendy Bima Mahardana; Ibra Dewandono; Afan Ridlo Abdulloh; Mochamad Akbar; Moch Okhynawa; Ronaldin Lindimeha (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
Concrete is a form of construction in the form of a composite material consisting of a mixture of fine aggregate, coarse aggregate, cement, and water. However, in certain cases, the concrete application is often a problem, especially the lack of a minimal amount of coarse aggregate material, increasing material prices. Recycled concrete aggregate (RCA) is an embodiment of concrete composed of recycled materials. Recycled material is obtained from fragments or remnants of the demolition of unused concrete. The method used to make concrete from the constituent materials using concrete waste as coarse aggregate per the rules of science is experimental. The tests are the aggregate moisture content test, the mud content test, the coarse aggregate abrasion test, the slump test, and the concrete compressive strength test at 28 days of treatment. The compressive strength results showed that the normal concrete sample could reach FC 18.53 MPa. The concrete sample using recycled coarse aggregate reached FC 23.79 MPa, so using recycled materials for manufacturing concrete can achieve the planned target